The Urgency of Formulating Legislation On The Protection of HIV/AIDS Patients From A Human Rights Perspective - Indiyarto, Fadhil Muhammad; Lewoleba, Kayus Kayowuan (Fakultas Hukum, Universitas Islam Bandung, 2024)
The state has an obligation to guarantee the human rights of all members of society, including people living with HIV/AIDS (PLWHA). However, in practice, the human rights of PLWHA are often violated through various forms of discrimination. One way the state provides legal guarantees is by enacting legislation related to specific issues. This is the objective of the author's research: to examine PLWHA from a human rights perspective and the urgency of formulating legislation in the context of legal protection for people living with HIV/AIDS. The author employs a Normative Juridical research method in this study. The findings of the research indicate that people living with HIV/AIDS, or PLWHA, still possess human rights despite often being targets of human rights violations in Indonesia. Consequently, the formation of legislation for the legal protection of PLWHA must be expedited to ensure their legal protection.